ОПЕРАТИВНИЙ АНАЛІЗ ПІСЛЯАВАРІЙНОГО СТАНУ РОЗПОДІЛЬНИХ ЕЛЕКТРИЧНИХ МЕРЕЖ ЗАСОБАМИ ІНТЕЛЕКТУАЛЬНОЇ СИСТЕМИ - Буткевич , О.Ф.; Парус , Є.В. (Інститут електродинаміки Національної академії наук України, 2018)
The peculiarities of the approach used in the intelligent system for solving the problem of the operational analysis of the postemergency state of distribution electrical networks to support the dispatcher's decision concerning power supply recovery are presented. To solve the problem the tele signals indicating at the facts of operation of the breakers and relay protection and automation devices are used. References 4, figures 4.